The mediating role of lean soft tissue in the relationship between somatic maturation and bone density in adolescent practitioners and non-practitioners of sports - Agostinete, Ricardo R. [UNESP]; Werneck, André O.; Maillane-Vanegas, Santiago [UNESP]; Gracia-Marco, Luis; Ubago-Guisado, Esther; Constable, Annie M.; Fernandes, Romulo A. [UNESP]; Vlachopoulos, Dimitris (MDPI, 2021)
This study aimed to identify the mediating effect of lean soft tissue (LST) in the association between somatic maturation and areal bone mineral density (aBMD) in adolescents by sex and sport participation. The sample included 558 adolescents (401 males, mean age of 14.0 years) that were practitioners of sports (11 sport modalities, n = 402) and a non-sport group (n = 157). Somatic maturation was assessed by using a validated peak height velocity prediction equation. Dual-energy X-ray absorptiometry (DXA) was used to assess aBMD (upper and lower limbs, spine and total body less head—TBLH) and LST. For both sexes, LST mediated the association between somatic maturation and aBMD at all skeletal sites (mediation percentage ranging from 36.3% to 75.4%). For sport and non-sport groups, the LST also mediated the association between somatic maturation and aBMD at all skeletal sites (mediation percentage ranging from 51.6% to 85.6%). The direct effect was observed in all groups, except for lower limbs and TBLH in the non-sport group. The association between somatic maturation and aBMD was mediated by LST in adolescents of both sexes and re-gardless of involvement in organized sports. Our findings highlighted the role of improving LST to mitigate the association of somatic maturation with aBMD.
Keywords: Bone health; Exercise; Team sport; Youth